Pengaruh kecerdasan adversitas dan prestasi kerja terhadap profesionalitas guru - Ermina Srihartini; Rhini Fatmasari; Tita Rosita (Jurnal Konseling dan Pendidikan, 2021)
This study aims to analyze the effect of adversity intelligence and work performance on the professionalism of teachers .This research is quantitative correlational research. The sample was determined using a random sampling technique of 135 people. The instrument used was a questionnaire of adversity intelligence, work performance, and teacher professionalism. The data analysis tool was performed using the Structural Equation Modeling Method (SEM LISREL 8.30). The results showed that there was a significant effect of adversity intelligence on teacher professionalism .There is a significant effect of adversity intelligence on work performance. There is a significant effect on work performance on teacher professionalism. The results of this study imply that adversity intelligence and work performance are two factors that affect teacher professionalism.